Architecture, Structure, and Loads: A Moment of Change? - Uihlein, Marci S. (Enquiry The ARCC Journal for Architectural Research, 2012)
Architecture and building structure have a unique, complicated, and intertwined history. Architectural innovations can drive the development of structural systems and structural advancements can push architecture forward. Rem Koolhaas, writing about one of his primary engineering collaborators in 2002, stated that this collaborator "almost single"handedly shifted the ground in engineering ” a domain which the earth moves very rarely ” and therefore enabled architecture to be imagined differently.”1 There are two ideas embedded in this quote. The first is that building structure and those who design it are entrenched in a way of practice that seldom varies. The second is that the view of structure is changing and this change has the potential to allow architecture to make a significant transformation. Ten years later, the question remains, is structure changing, and if so, how and what metrics can be used to establish this? Digital technology and fabrication advancements have led to an exploration of building structure and material. Architects are creating buildings once thought impossible to build. Through experimentation, new forms and roof systems are being created. Does this form creation have a larger meaning? One indicator of this might be found in the way loads and load paths are conceived. When starting a project, the primary determinants are the understanding of the loads created by the engineer and the selection of a structural system to support them. Can an examination of loads be used to evaluate change in structure? This investigation will begin with a brief discussion of loads and will analyze two recently constructed works as case studies. The structural systems in these buildings will be examined to see if the conception of loads and the philosophy behind the system is evolving.